DEVELOPMENT OF A LOCAL WISDOM-BASED E-MODULE USING THE CULTURALLY RESPONSIVE TEACHING (CRT) APPROACH TO IMPROVE CRITICAL THINKING SKILLS AND CHEMISTRY LEARNING OUTCOMES ON REACTION RATE MATERIAL - Praksedes Yeni Kore; Tiurlina Siregar; Albaiti (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2026)
The purpose of this study was to describe how to create e-modules based on local wisdom, analyze the feasibility of e-modules, evaluate improvements in critical thinking skills, and evaluate improvements in outcomes. The research method employed was Research and Development (R&D) using the 4D procedural model (define, design, development, disseminate). The instruments used in this study included an e-module feasibility validation sheet, a critical thinking skills test, and a learning outcomes test. The e-module data were analyzed empirically using SPSS version 22. The sampling technique applied was purposive sampling, with a sample consisting of 34 eleventh-grade students of SMA Negeri 2 Serui. The results of the study indicated that the e-module was developed through the stages of preparation, production, and finalization by utilizing Canva software and the Heyzine website. The feasibility analysis showed that the average validator assessment score was 92.36%, categorized as highly feasible. The local wisdom-based e-module employing the CRT approach on reaction rate material was practical for use and effective in improving students’ critical thinking skills and learning outcomes, with N-Gain scores of 0.72 (high category) and 0.76 (high category), respectively.